2022
DOI: 10.1002/ldr.4160
|View full text |Cite
|
Sign up to set email alerts
|

Land and water conservation technologies for building carbon positive villages in India

Abstract: Continuous and unabated land degradation in India is a threat to agricultural sustainability while increasing temperatures, changing rainfall patterns and precipitation intensification are going to further aggravate degradation in future. The timely adoption of integrated land and water conservation technologies minimises erosion and provides significant adaptation and mitigation co‐benefits. The objectives of this study were to assess the mitigation potential of soil and water conservation technologies and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Deforestation and forest degradation are recognized as critical environmental issues that contribute significantly to global greenhouse gases (GHGs) emissions (Fujisaki et al, 2020; Mattsson et al, 2012; Sheng et al, 2016). The United Nations Framework Convention on Climate Change (UNFCCC) introduced an international management mechanism to confront climate change, namely Reducing Emissions from Deforestation and Forest Degradation (REDD+) (Maraseni et al, 2020; Sheng, 2020; Srinivasarao et al, 2022). In recent years, REDD+ projects have been considered as a worldwide policy to avoid deforestation in developing countries (Atela et al, 2014; Lin et al, 2014; Maraseni et al, 2014; Wei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation and forest degradation are recognized as critical environmental issues that contribute significantly to global greenhouse gases (GHGs) emissions (Fujisaki et al, 2020; Mattsson et al, 2012; Sheng et al, 2016). The United Nations Framework Convention on Climate Change (UNFCCC) introduced an international management mechanism to confront climate change, namely Reducing Emissions from Deforestation and Forest Degradation (REDD+) (Maraseni et al, 2020; Sheng, 2020; Srinivasarao et al, 2022). In recent years, REDD+ projects have been considered as a worldwide policy to avoid deforestation in developing countries (Atela et al, 2014; Lin et al, 2014; Maraseni et al, 2014; Wei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SC not only maximizes the prevention of soil erosion, but also yields evident ecological benefits, such as reducing carbon loss due to soil erosion and increasing the level of carbon sequestration in vegetation systems (Srinivasarao et al, 2022). The impact of SC on VCS can be manifested as follows: on the one hand, SC indirectly affects the carbon sequestration capacity of vegetation by altering soil physicochemical properties related to soil fertility, such as water holding capacity, nutrient conditions, and topsoil thickness (Bouchoms et al, 2019), and by promoting the normal colonization, survival, and growth of plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SC enhances the capability of the soil to maintain biodiversity above and below ground (Orgiazzi & Panagos, 2018); it also contributes to the sequestration of carbon and nitrogen, thereby providing additional ecosystem services (Eekhout & de Vente, 2020). Recent results have shown that SC is effective in reducing CO 2 emissions and increasing carbon sinks by enhancing vegetation resilience (Srinivasarao et al, 2022). Therefore, SC is an ecologically valuable solution for achieving increased vegetation carbon sinks and mitigating global climate change.…”
Section: Introductionmentioning
confidence: 99%